Urgensi Pendekatan Multimodal Berbasis E-Book Terhadap Motivasi Membaca Siswa Sekolah Dasar - Liana Mumrikoh; Djono, Djono; Drajati, Nur Arifah (Universitas Pendidikan Ganesha, 2023)
Reading motivation is an important predictor of reading achievement in elementary school. Electronic book or digital book is one of the media that students can always access by technological assistance. This study aims to determine the urgency and potential of developing a teaching material product in the form of E-Book based multimodal approach on reading motivation for elementary school students. This research is included in the mixed method approach using explanatory sequential design. The research subjects consisted of teachers and 79 students in fifth grade. The data collected in this study are qualitative and quantitative data. Qualitative data was collected using observation techniques, and interviews whose instruments were observation sheets and interview guidelines. Quantitative data was collected using non-test techniques, namely questionnaires and followed by questionnaires as instruments. Furthermore, the research data will be analyzed descriptively with interactive analysis through data collection, data reduction, data presentation, and conclusion drawing. The results showed that during the implementation of learning, teachers only used teaching materials in the form of printed books that causes students to be lazy to read and student responses stated that they needed interesting ICT-based teaching materials to increase engagement, reading habit and motivation to read which in this case as many as 94% of students agreed if there was development in interactive teaching materials in e-book format for language learning.Therefore, this study concluded that to encourage good reading habits among students, schools especially teachers should provide access to learning using ebooks and sufficient facilities to accommodate all students. Implication of this study can be a reference for teachers to develop similar electronic media. Librarians should intensify their efforts to create more reading awareness among students.